Motivasi Orang Tua Memilih Pondok Pesantren Sebagai Sarana Mendidik Moral Anak (Studi Kasus Di Pondok Pesantren Putri Darussalam Selatan Blokagung Tegalsari Banyuwangi) - Mamlukhah Mamlukhah (Jurnal Darussalam: Jurnal Pendidikan, Komunikasi dan Pemikiran Hukum Islam, 2017)
Motivation parents are very supportive of the success of a child, the parents give motivation to the child, then the child will be more enthusiasm in learning. Thus the factors that motivate parents so choose boarding school as a means of educating morals. This study used a qualitative descriptive approach, using methods of observation, questionnaire, interview, and documentation is component of data collection methods. After analyzing the data collected, it was found that (1). Motivation parents want to instill religious values as a child in the child obtain a score of 97 people who were in the interval 14-18. (2). Motivation parents by educational level obtained a score of 100 persons who did interval 10-12. (3). Motivation parents according to the busyness factor parents to obtain a score of 70 persons who did interval 7-9. (4) .Motivasi parents by a factor of economic conditions and income parents to obtain a score of 49 people who did interval 10-12. (5). Motivation parents according to the quality of education obtained a score of 97 people who did interval 10-12. (6). Motivation parents by charismatic obtain a score of 68 people who did interval 5-6. (7). Motivation parents according to environmental factors gain score 81 people who did interval 17-21. (8). Motivation parents according to the proximity of the schools with residence obtained a score of 50 people who did interval 5-6. (9). Motivation parents according to the characteristics of the boarding school obtained a score of 90 charcoal are did interval 5-6.